Benford's law and Chinese banks' non-performing loans - Karlo Kauko (Bank of Finland, Institute for Economies in Transition (BOFIT), 2019)
Benford's law states that the leading significant digits in real-world data sets, provided the data span several orders of magnitude, are not normally uniformly distributed. Deviations from this law may indicate human intervention, even fraud. The data on Chinese banks' non-performing loans has sometimes deviated from Benford's law. Up to 2012, the frequency of ones as leading significant digits was lower than predicted by Benford's law. Surprisingly, the number of ones well exceeded the expected level for large and government-owned banks during 2015–2018.
URN:NBN:fi:bof-201912201724
Keywords: C46; G21; 330